การเปรียบเทียบการปรับสภาพของเส้นใยนุ่นโดยใช้โซเดียมไฮดรอกไซด์และเอนไซม์ไลเปสสำหรับการผลิตเยื่อแบบโซดา - ทิพวรรณ หอมไม่วาย (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Kapok fiber can be one of the potential fiber sources for papermaking because paper containing kapok pulp provided excellent tensile strength. Due to the waxy cutin on the kapok fiber surface making kapok fibers hardly dampened, kapok fibers needed to be immersed in water for at least 3 weeks. It was hypothesized that the waxy cutin coating kapok fiber surface might be removed by chemical and biological pretreatment. Therefore, immersing time of kapok fibers before soda pulping could be shorten.Thus, the objective of this research was to study the conditions of alkali pretreatment in terms of sodium hydroxide 5% and 10% based on oven dried (O.D.) fiber weight for 1, 2 and 3 weeks of immersion. For biological pretreatment lipase at 0.25% and 0.5% based on the O.D. fiber weight (or 250 LU/g and 500 LU/g of O.D. fiber weight respectively) for 1, 3 and 5 hours. Both pretreatments impose effects on soda pulping efficiency of kapok fibers. After the pretreatments, kapok fibers were pulped using soda process with 20% of sodium hydroxide based on O.D. fiber weight which was the optimal dosage determined from the experiment at 120 °C for 2 hours. Compared to the control experiment without the pretreatments before soda pulping, it was found that the sodium hydroxide pretreatment did not significantly affected pulp yield while the lipase pretreatment decreased pulp yield. Both pretreatments decreased residual alkali which implied that the pretreatment used the lower pulping chemicals. Both pretreatments also caused the lower lignin content. It was also discovered that sodium hydroxide pretreatment provided the higher tensile, burst and tear strength while lipase pretreatment offered the higher tensile and burst with the lower tear strengths.